2015
DOI: 10.1111/vec.12409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between clinical variables and thromboelastographic findings in dogs with protein‐losing nephropathy

Abstract: Hypercoagulability was prevalent in dogs with PLN but could not be predicted based upon the presence or degree of proteinuria, systemic arterial hypertension, hypoalbuminemia, or low AT activity. The prevalance of thromboembolism was low in this population with PLN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 38 publications
1
38
1
Order By: Relevance
“…Overall, CBVD exposure, particularly exposure to Rickettsia and Ehrlichia species and B burgdorferi , was frequent among proteinuric dogs in our study. Establishing a direct cause‐and‐effect relationship between positive CVBD test results and proteinuria will require both controlled, prospective epidemiologic studies as well as experimental studies . With recent standardizations in renal histopathology, interpretation of renal biopsy results obtained from proteinuric dogs may allow for more precise interpretation of CVBD test results .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, CBVD exposure, particularly exposure to Rickettsia and Ehrlichia species and B burgdorferi , was frequent among proteinuric dogs in our study. Establishing a direct cause‐and‐effect relationship between positive CVBD test results and proteinuria will require both controlled, prospective epidemiologic studies as well as experimental studies . With recent standardizations in renal histopathology, interpretation of renal biopsy results obtained from proteinuric dogs may allow for more precise interpretation of CVBD test results .…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is an important clinical finding and is not only a marker of nephropathy but also a prognostic factor for progression of chronic kidney disease . Proteinuria is related to decreased survival in azotemic and non‐azotemic dogs, and decreasing proteinuria improves survival .…”
Section: Introductionmentioning
confidence: 99%
“…Thromboemboli were found in up to 38% of dogs with renal amyloidosis with both arterial and venous locations with pulmonary arterial thrombi being the most common . The incidence of thromboembolic complications in people with nephrotic syndrome has been reported as high as 44% and a recent thromboelastography (TEG) study in dogs with PLN found 89% of dogs were hypercoagulable by TEG analysis . Dogs with nephrotic syndrome are thought to be hypercoagulable due to urinary loss of antithrombin, hyperfibrinogenemia as a result of ongoing inflammation, and platelet hyperaggregability secondary to hypoalbuminemia .…”
Section: Discussionmentioning
confidence: 99%
“…Hypovolemia leading to vascular stasis may also be a predisposing factor to thromboembolism in some PLN patients . In most dogs with PLN, the UPC ratio, serum albumin concentration, and plasma antithrombin activity are not predictive of thromboembolic complications and do not predict TEG‐based hypercoagulability . The lack of ability to identify one marker that predicts hypercoagulablity in dogs with PLN suggests the predisposition is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Protein‐losing nephropathy (PLN) in dogs is associated with a hypercoagulable state and thromboembolic risk . The true prevalence of thromboembolic complications in PLN dogs is difficult to ascertain but has been reported to be more than 40% in previous studies .…”
Section: Introductionmentioning
confidence: 99%